2008
DOI: 10.1017/s0031182008004137
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan-protozoan parasite co-infections and host body weight in St Kilda Soay sheep

Abstract: S U M M A R YFor hundreds of years, the unmanaged Soay sheep population on St Kilda has survived despite enduring presumably deleterious co-infections of helminth, protozoan and arthropod parasites and intermittent periods of starvation. Important parasite taxa in young Soay sheep are strongyles (Trichostrongylus axei, Trichostrongylus vitrinus and Teladorsagia circumcincta), coccidia (11 Eimeria species) and keds (Melophagus ovinus) and in older animals, Teladorsagia circumcincta. In this research, associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 42 publications
(75 reference statements)
2
54
1
Order By: Relevance
“…Giemsa-stained trypanosomes (trypomastigotes) from a fibroblast co-culture incubated at 37°C. lambs, with a prevalence of 82% recorded from the underbelly; the prevalence fell to 28% in yearlings and 12% in adults (Craig et al 2008). Here, all but 1 of the keds taken from lambs were positive for trypanosome infection by PCR or dissection, and a lower prevalence was evident in keds removed from yearlings and adults.…”
Section: Discussionmentioning
confidence: 68%
“…Giemsa-stained trypanosomes (trypomastigotes) from a fibroblast co-culture incubated at 37°C. lambs, with a prevalence of 82% recorded from the underbelly; the prevalence fell to 28% in yearlings and 12% in adults (Craig et al 2008). Here, all but 1 of the keds taken from lambs were positive for trypanosome infection by PCR or dissection, and a lower prevalence was evident in keds removed from yearlings and adults.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we accounted for age in all models, which is the key driver of between-individual variation in parasite infracommunity (the species composition of a host individual's parasite fauna) in this population [61]. There is also evidence in this population that coinfection with prevalent Eimeria protozoan parasites does not affect the association between body weight and strongyle FEC [37]. Finally, as is discussed in more detail below, all the evidence collected thus far suggests that the relatively intolerant individuals identified by this analysis are not merely paying a cost of resistance: analysis has revealed that body weight is either not significantly associated or is positively associated with antibody responses, including those specific to Teladorsagia circumcincta [52],[62], suggesting that nematode-resistant sheep do not pay a cost in terms of reduced body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Strongyle-specific antibody titre is strongly negatively associated with strongyle FEC [52], and thus, this result suggests that there is no association between our measure of tolerance and our best measure of immunological resistance in this population. In addition, mean tolerance (the association between strongyle burden and body weight) is independent of the burden of coinfecting intestinal protozoa [37]. The diverse effector mechanisms of T-helper 2–mediated immunity, which include anthelmintic and tissue-repair processes [69],[70], suggest that resistance and tolerance to nematode infections may occur in concert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in free ranging populations of springbok, strongyle burdens were only associated with reduced body condition only in adult females, while coccidia burdens were not associated with condition in any age category (Turner et al, 2012). In Soay sheep, both coccidia and nematodes were negatively associated with August weight in adults, but only nematodes were negatively associated with condition in yearlings and lambs (Craig et al, 2008). We observed lower body condition with increasing nematode burdens in all ages, and reductions in condition with coccidia burdens only in senescent buffalo.…”
Section: Discussionmentioning
confidence: 99%